2015
DOI: 10.1016/j.bcmd.2015.02.001
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphic variations influencing fetal hemoglobin levels: Association study in beta-thalassemia carriers and in normal individuals of Portuguese origin

Abstract: Three major loci have been associated with HbF levels, including -158C/T (XmnI) at HBG2 promoter region, and several polymorphisms at BCL11A intron-2 and HBS1L-MYB (HMIP) intergenic region. Mutations in the KLF1 gene were recently associated with increased HbF levels. This study aims to evaluate whether genetic variability at these loci influence HbF levels in β-thalassemia carriers and in normal individuals of Portuguese origin. Sixty five β-thalassemia carriers, HbF levels ranging from 0.2% to 9.5%, and 60 i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 33 publications
2
12
1
Order By: Relevance
“…In respect to this point, our last conclusion is that the Aγ(+25 G->A) and Gγ-globin-XmnI polymorphisms might be associated with high HbF in erythroid precursor cells isolated from the β 0 39/β 0 39 thalassemia patients (Fig. 4 ), in agreement with several studies suggesting the association between XmnI polymorphism and high HbF production [ 18 , 24 , 34 , 35 ].…”
Section: Discussionsupporting
confidence: 89%
“…In respect to this point, our last conclusion is that the Aγ(+25 G->A) and Gγ-globin-XmnI polymorphisms might be associated with high HbF in erythroid precursor cells isolated from the β 0 39/β 0 39 thalassemia patients (Fig. 4 ), in agreement with several studies suggesting the association between XmnI polymorphism and high HbF production [ 18 , 24 , 34 , 35 ].…”
Section: Discussionsupporting
confidence: 89%
“…In the developing fetus, HBG1 and HBG2 code for two gamma chain proteins, which along with corresponding alpha chains, make up fetal hemoglobin (HbF). At birth, HbF undergoes replacement by mature adult hemoglobin (HbA), in a process that continues over the first 6 months of age (19). As shown in Table I, the mean expression levels of HBG2 decreased significantly with age as HbA replaced HbF.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, several authors found a significant associated between Xmn I polymorphism and HbF levels in Chinese, Brazilian, and Portuguese β-thal carriers. [ 12 22 25 29 30 ] On the other hand, an association could only be documented with the combination of Xmn I and (AT) x (T) Y polymorphisms in Italian carriers. [ 15 ] Conversely, other investigators failed to demonstrate an association between this polymorphism and HbF in carriers.…”
Section: Discussionmentioning
confidence: 99%
“…The latter has been found to contribute to variability in HbF among β-thal carriers in other populations. [ 12 29 ] Other culprits that may have played a role in this variability as documented by other studies in other populations and need scrutiny are the β-genotype and alpha gene triplication. [ 13 14 32 ]…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation